2023
DOI: 10.1101/2023.02.20.529031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community composition and the environment modulate the population dynamics of type VI secretion in human gut bacteria

Abstract: Understanding the relationship between the composition of the human gut microbiota and the ecological forces shaping it is of high importance as progress towards therapeutic modulation of the microbiota advances. However, given the inaccessibility of the gastrointestinal tract, our knowledge of the biogeographical and ecological relationships between physically interacting taxa has been limited to date. It has been suggested that interbacterial antagonism plays an important role in gut community dynamics, but … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 90 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…Our work demonstrates that the fitness costs associated with constitutive expression of the Type VI Secretion System in V. cholerae are low, and will often be imperceptible to natural selection, even when considering the additional costs incurred by friendly fire. In contrast, recent work from others has shown that T6SS was strongly selected against within animal models [10]. Together, these results suggest that while the expression of the T6SS is not metabolically costly, it may nonetheless be costly to express in certain environments (e.g., through triggering host immune response [19], or via emergent consequences of changed ecological dynamics).…”
Section: Main Textmentioning
confidence: 89%
See 2 more Smart Citations
“…Our work demonstrates that the fitness costs associated with constitutive expression of the Type VI Secretion System in V. cholerae are low, and will often be imperceptible to natural selection, even when considering the additional costs incurred by friendly fire. In contrast, recent work from others has shown that T6SS was strongly selected against within animal models [10]. Together, these results suggest that while the expression of the T6SS is not metabolically costly, it may nonetheless be costly to express in certain environments (e.g., through triggering host immune response [19], or via emergent consequences of changed ecological dynamics).…”
Section: Main Textmentioning
confidence: 89%
“…Our work demonstrates that the fitness costs associated with constitutive expression of the Type VI Secretion System in V. cholerae are low, and will often be imperceptible to natural selection, even when considering the additional costs incurred by friendly fire. In contrast, recent work from others has shown that T6SS was strongly selected against within animal models [10].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“… 29 In the mouse gut, the abundance of T6SS producers will increase while competing with sensitive competitors and significantly decrease if co-existent with resistant or non-interactive strangers. 35 These findings suggest that GA3 T6SS-dependent competition mechanism within a microbial community is intricate and heavily relies on the surrounding microbial lineages inhabiting the same ecological niches, as well as their sensitivity to T6SS antagonistic actions ( Figure 1 ). A genomic and metagenomic data based study indicated that GA2 and GA1 T6SS are widespread in Bacteroidales isolated from gut but absent in bacteria isolated from oral cavity or vagina, suggesting fitness advantage conferred by T6SS in gut environment 36 .…”
Section: Interference Competitionmentioning
confidence: 97%
“…The incentive for bacteria to evolve such a genomic switch, could be the possibility to deactivate the expression of dispensable and energy-costly molecular machineries. Recent studies on Vibrio, Pseudomonas, and Bacteroides strains suggest that T6SS activity does in fact come with a fitness cost and it may be beneficial to regulate its activity (Drebes Dörr et al, 2022;Septer et al, 2023;Perault et al, 2020;Robitaille et al, 2023).…”
Section: Insertion Sequence Elements: Regulation Of Ixotrophy Dependi...mentioning
confidence: 99%